ANALISIS PENGARUH INVESTASI DAN TENAGA KERJA TERHADAP NILAI INDUSTRI SEKTOR INDUSTRI MANUFAKTUR DI JAWA TIMUR TAHUN 1999-2018 - Linda Rukmana cans; Wahyu Hidayat Riyanto (Program Studi Ekonomi Pembangunan, 2020)
The purpose of this study was to determine the effect of investment and labor on the production value of the manufacturing industry sector in East Java 1999-2018. The number of samples used is 20 years. The method used is a quantitative approach using secondary data obtained from data from the Central Statistics Agency (BPS). The analytical tool used is multiple linear regression. Data is processed through E-views. The results showed that investment and labor had a significant positive effect on the value of production in the manufacturing industry sector. In this study the researcher has a limitation of only using 20 years and only using investment and labor variables as an independent variable so that it can influence the research results. The next researcher is expected to be able to develop the number of variables and be able to add observation time.